Avifauna (Non Passeriformes) of Santa Cruz province, Patagonia (Argentina): Annotated list of species - Darrieu, Carlos Aquiles (2008)
The birds of Santa Cruz Province, Argentina, are analyzed based on three main sources: specimens housed in the Museo Argentino de Ciencias Naturales of Buenos Aires, in the Félix de Azara Collection, Buenos Aires (CFA), in the Museo de La Plata, La Plata, in the Fundación Miguel Lillo, Tucumán and in the National Museum of Natural History (USNM); from bibliographical citation which include precise localities, and from field observations. A list of 150 species belonging to 33 families is presented. First records with precise localities are provided for nine species. New localities are cited for 114 species.